Being in the World Locally: Degrowth Business, Critical Realism, and Humanistic Geography - Nesterova, Iana (Frontiers in Sustainability, 2022)
It has been argued that to achieve a genuinely sustainable society, our mode of being in the world needs to change. Understanding macro visions such as the desirable size of our economies remains essential, but concrete ways of being in the world which unite such aspects of our existence as the self, being with others (humans and non-humans) and being in and with nature deserve a much closer attention. Hence, I propose focusing our attention on being once again. But rather than contemplating being as an abstract philosophical category, this paper looks at being in the world in this dual sense: we are part of the cosmos, of the web of existence and at the same time we are in the world locally, in concrete places and locations characterised by particular cultural attributes, political-economic systems, climate and landscape. This nature of being applies to individual humans and human organisations. This paper focuses specifically on business as one type of organisations. I employ the concept of degrowth business, the philosophy of critical realism and humanistic geography as lenses to enhance and deepen our understanding of what it could mean and look like for a business to be in the world locally and more sustainably. To understand what it could mean and look like in reality, I offer a case of a firm from Northern Sweden specialising in vertical hydroponic agriculture.